KAJIAN SEBARAN INDUSTRI GALAMAI DI KOTA PAYAKUMBUH - puja rizki bahari; Rery Novio (JURNAL BUANA, 2021)
ABSTRACTThis study aims to analyze 1) the distribution pattern of the galamai industry in the city of Payakumbuh, 2) the category of the Galamai industry in the city of Payakumbuh, 3) the pattern of marketing coverage of the galamai industry in the city of Payakumbuh. This type of research is descriptive quantitative. The study population was 16 industries. The sampling technique was total sampling. Data collection techniques were interviews, questionnaires and observations. The data analysis technique used nearest neighbor analysis, proportion and spatial diffusion theory. Based on the research results, 1) the distribution pattern of the galamai industry with a ratio of 0.987141 means that it has a random pattern (random). 2) natural capital industry scenario, 56.25% capital <IDR 1,000,000, 100% equity. 100% raw material comes from Payakumbuh City, 43.75% using raw materials 10Kg-20Kg. 56.25% of industries with a workforce of> 7 people, 100% coming from Payakumbuh, 75% of wages of Rp.50,000-Rp.100,000, the status of permanent workers is 87.5%. 75% produce 20Kg-40Kg, 50% of industry produce IDR 2,000,000-IDR 5,000,000. Marketing in 2010, 100% with telephone communication, 2015 using Facebook 12.5%, 2020 with the help of WhatsApp communication 87.5% and Instagram 12.5%. 3) the marketing outreach pattern undergoes a diffusion process that takes place every year, which is called expansion with the help of effective online marketing because distance is no longer an obstacle to marketing expansion.Key words: distribution pattern, characteristics, marketing